IMMUNOLOGICAL MEMORY: THE ROLE OF REGULATORY CELLS (TREGS) - E. K. Oleinik; A. V. Churov; V. M. Oleinik (Медицинская иммунология, 2018)
Memory T cells are necessary for development of the immune response and represent one of the most numerous population of human T lymphocytes. On the contrary, suppressive regulatory T cells (Tregs) may terminate the immune response and help to maintain tolerance to self-antigens. These important groups of cells are consisting of different subpopulations and retaining throughout life. However, today there is yet no clear understanding of how the relations between these two groups of cells are formed. In this work we consider possible ways of development and maintenance of CD4+ T cell memory and role of Tregs in these processes. Mechanisms of a differentiation of memory T cells, Tregs and recently described memory Tregs are discussed. The functional and genetic characteristics of these cells are compared. Division of cells according to the functional profile allows drawing parallels between memory T cells and Tregs. These two groups are consisted of central circulating populations (Tc), effector which can migrate toward specific tissues (Te) and tissue-resident cells (Tr), which are staying in peripheral tissues. The similar structural organization of Tregs and memory T cells, existence of transitional forms of tissue-resident Treg subpopulations with properties of memory cells assumes existence of close interrelation between these groups of lymphocytes. The conversion of CD4+ memory T cells into FoxP3-expressing Tregs is one of possible mechanisms of communication between these two groups. The memory Treg-cells with T cell and memory Treg-cell properties can represent a transitional stage of differentiation. On the other side, Treg cells can differentiate independently of memory T cells and accumulate during life in the form of memory Treg cells. The supressor function of Tregs is also necessary as well as function of memory T cells to develop the immune response. It is possible, that a subset of Treg cells undergoes selection in thymus and constitutively express TCR-receptors having affinity with peripheral tissues. Further, these committed cells can be settled into tissues and become tissue-resident Treg cells which maintain regional T cell memory. Tregs can represent the “mirror image” of the structural organization of memory T cells, but with the return sign – the sign of suppression. The quantitative ratio of Tregs and memory T cells (CD4+CD45RO+CD25hiFoxP3+/CD4+CD45RO+CD25-FoxP3-), perhaps, is important criterion for functional assessment of immune system. The balance between these functionally opposite cell subsets has to provide stable functioning of immune system.